MathOverflow is a question and answer site for professional mathematicians. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top


The following question appears as a step in my proof. It seems easy but somehow I have not been able to prove this. I could solve few special cases though. Any help in this context is welcome.

Thank you.


Let $u,v\in \Lambda^2$ be such that $$ u\wedge u=-v\wedge v\neq 0. $$ Does there exist $\alpha,\beta\in\mathbb{R}$ such that $$ (\alpha u+\beta v)\wedge (\alpha u+\beta v)=0\text{ and }\alpha u+\beta v\neq 0? $$

share|cite|improve this question
up vote 4 down vote accepted

I assume that you are working with a real vector space. Otherwise, you could take $v=iu$ and get a counterexample.

Let $u$ and $v$ in $\Lambda^2(V^\ast)$ satisfy $u^2 = - v^2 \not = 0$. Since $u^2\not=0$, it follows that, for any $a\in V^\ast$, the equation $a\wedge u = 0$ implies $a=0$, with a similar statement for $v$. For $x\in V$, I will let $i_x$ denote interior product with $x$.

Now, if $x\in V$ satisfies $i_x(u^2)=0$, then $i_xu\wedge u = 0$, so $i_xu=0$. Applying the same argument to $v$ and using $u^2 = - v^2$, one sees that $i_xu=0$ if and only if $i_xv=0$. Thus, $u$ and $v$ have the same kernel, and hence the same rank, and so we are reduced to the case in which $u$ and $v$ are symplectic forms (i.e., nondegenerate) on $V$.

In the case that the dimension of $V$ is $4$ (i.e., when $u^3 = v^3 = 0$), the result is trivial, so assume that the dimension of $V$ is bigger than $4$. Then for any $a\in V^\ast$, it follows that the $3$-forms $a\wedge u$ and $a\wedge v$ have only $a$ as a linear factor. However, if $x\in V$ is nonzero, it follows from our assumption that $i_xu\wedge u = - i_xv\wedge v$, so $i_xu$ and $i_xv$ must be linearly dependent (and nonzero) for all nonzero $x\in V$. From this, it easily follows that there is a nonzero constant $c$ such that $i_xv = c\ i_xu$ for all $x\in V$, which implies that $v = c\ u$, which, in turn, implies that $v^2 = c^2\ u^2 \not= - u^2$, so this case cannot happen.

share|cite|improve this answer
Thanks a lot!!! – tatin Nov 15 '12 at 4:35

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.